A whole-genome screen identifies Salmonella enterica serovar Typhi genes involved in fluoroquinolone susceptibility. (8th June 2020) - Turner, A Keith; Eckert, Sabine E; Turner, Daniel J; Yasir, Muhammud; Webber, Mark A; Charles, Ian G; Parkhill, Julian; Wain, John
Abstract: Objectives: A whole-genome screen at sub-gene resolution was performed to identify candidate loci that contribute to enhanced or diminished ciprofloxacin susceptibility in Salmonella enterica serovar Typhi. Methods: A pool of over 1 million transposon insertion mutants of an S. Typhi Ty2 derivative were grown in a sub-MIC concentration of ciprofloxacin, or without ciprofloxacin. Transposon-directed insertion site sequencing (TraDIS) identified relative differences between the mutants that grew following the ciprofloxacin treatment compared with the untreated mutant pool, thereby indicating which mutations contribute to gain or loss of ciprofloxacin susceptibility. Results: Approximately 88% of the S. Typhi strain's 4895 annotated genes were assayed, and at least 116 were identified as contributing to gain or loss of ciprofloxacin susceptibility. Many of the identified genes are known to influence susceptibility to ciprofloxacin, thereby providing method validation. Genes were identified that were not known previously to be involved in susceptibility, and some of these had no previously known phenotype. Susceptibility to ciprofloxacin was enhanced by insertion mutations in genes coding for efflux, other surface-associated functions, DNA repair and expression regulation, including phoP, barA and marA . Insertion mutations that diminished susceptibility were predominantly in genes coding for surface polysaccharide biosynthesis and regulatory genes, including slyA, emrR, envZ and cpxR . Conclusions: A genomics approach has identified novel contributors to gain or loss of ciprofloxacin susceptibility in S. Typhi, expanding our understanding of the impact of fluoroquinolones on bacteria and of mechanisms that may contribute to resistance. The data also demonstrate the power of the TraDIS technology for antibacterial research.